A matrioska em mutação: processos de subjetivação na docência em artes visuais - Backes, Francieli (2017)
This master thesis Is thought by a teacher in the visual arts that enhances the figure of matrioska, this doll, capable of composing itself in multiplicities that transit through these unstable territories of a moment that Bauman (2001) considers as "liquid modernity". The matrioska invites here to think with her, to deform her, to create with her this complex teaching complex, affected by the constant processes of subjectivation thought from Deleuze (2005) and Foucault (1984, 1985). These affections (ESPINOSA 2009) do not produce a meekness, but a boil of possibilities for the teaching act. In this context, a research based on bricolage is presented, where the mutations of this matrioska intend teaching practices in the scope of the complexity proposed by the studies of Morin (2013), practices that try to cross the borders constructed by the discourses of power. This paper proposes to problematize how the processes of subjectivation allow the teaching in the visual arts to think about the multiplicities and with the matrioskas.